Determinantes sociales de la salud en los accidentes de tránsito en Honduras 2019 (Revista Médica Hondureña, 2022)
Alejandra Polet Portillo Cálix https://orcid.org/0000-0002-9703-843XNora Rodríguez Corea https://orcid.org/0000-0003-1749-4556